2018
DOI: 10.1371/journal.pone.0204015
|View full text |Cite
|
Sign up to set email alerts
|

Persistent metamorphopsia associated with branch retinal vein occlusion

Abstract: PurposeTo investigate longitudinal changes in metamorphopsia associated with branch retinal vein occlusion.MethodsIn this prospective observational case series, we included 32 eyes (32 patients) with branch retinal vein occlusion and acute macular edema. Eyes were treated as needed with intravitreal ranibizumab injections for 12 months. At baseline and 1, 6, and 12 months after initiating treatment, metamorphopsia was quantified using M-CHARTS. Retinal morphology was examined through optical coherence tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
3
15
1
1
Order By: Relevance
“…A previous study demonstrated the mean number of injections within 12, 18, and 24 months was significantly higher in the TAE regimen than in the PRN regimen in the treatments for retinal vein occlusion patients [ 17 ]. In fact, the mean number of injections within 12 months (6.6 ± 1.7, median: 7 [IQR, 5–7]) in our TAE regimen was higher than the mean number of injections within 12 months (4.0 ± 1.8) reported in the previous study with the PRN regimen [ 8 ]. Further study is needed to optimize the TAE regimen in order to achieve a sustainable quality of vision for a longer time while lowering the patient, physician, and economic burden of BRVO-associated ME.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…A previous study demonstrated the mean number of injections within 12, 18, and 24 months was significantly higher in the TAE regimen than in the PRN regimen in the treatments for retinal vein occlusion patients [ 17 ]. In fact, the mean number of injections within 12 months (6.6 ± 1.7, median: 7 [IQR, 5–7]) in our TAE regimen was higher than the mean number of injections within 12 months (4.0 ± 1.8) reported in the previous study with the PRN regimen [ 8 ]. Further study is needed to optimize the TAE regimen in order to achieve a sustainable quality of vision for a longer time while lowering the patient, physician, and economic burden of BRVO-associated ME.…”
Section: Discussioncontrasting
confidence: 74%
“…Some studies about changes in metamorphopsia after anti-VEGF therapy with PRN regimen for BRVO-ME using M-CHARTS showed that the scores were not significantly decreased in the short term up to 6 months after induction even with ME improvement [ 6 , 7 , 9 ]. Osaka et al reported significant improvement in M-CHARTS scores at 1 month; however, the score worsened with no significant improvement at 12 months compared to baseline, and the mean cumulative number of ME recurrences was 3 ± 1.8 [ 8 ]. In contrast, our data show the improvement of the metamorphopsia with significant decrease of the mean M-CHARTS score was maintained up to 12 months, and the mean cumulative numbers of ME recurrences was 1.5 ± 1.8 (median: 1 [IQR, 0–2]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Naive 29 66.7 (8.2) 58.6 Retrospective, – 48 Lalinská et al [ 109 ] Czech Republic Ranibizumab 0.5 mg Three monthly injections then PRN regimen. Unclear 54 65 50 Retrospective, single-centre 12 Osaka et al [ 110 ] Japan Ranibizumab 0.5 mg Single injection then monthly PRN regimen Naive 32 68.1 (11.1) 53.13 Prospective, single-centre 12 Ozkaya et al [ 50 ] Turkey Ranibizumab 0.5 mg Three monthly injections then monthly PRN regimen. Naive 46 60.8 (8.7) 30.4 Retrospective, single-centre 24 Winterhalter et al [ 43 ] Germany Ranibizumab 0.5 mg Three monthly injections, then further sets of 3 monthly injections PRN if active disease.…”
Section: Resultsmentioning
confidence: 99%
“…Он связан с повреждением фоторецепторов и/или других клеток сетчатки в области макулы и возникающим при этом нарушением переработки оптической информации, которая в норме начинается уже в содержащем фоторецепторы наружном слое сетчатки и продолжается во время проведения импульсов через ее средний и внутренний слои [15]. Периферическая метаморфопсия описана при такой патологии, как возрастзависимая дегенерация макулы, макулярный отек, центральная серозная хориоретинопатия, макулярный разрыв сетчатки (перфорация сетчатки, макулярное отверстие), идиопатическая эпиретинальная мембрана и другие нарушения в зоне контакта стекловидного тела и сетчатки, пигментная дегенерация и отслойка сетчатки [10,[13][14][15][16][17][18][19].…”
unclassified